E-ADMINISTRATION SYSTEM FOR EFFECTIVITY SCHOOL ADMINISTRATION IN PANDEMIC COVID-19 ERA - Setyawan, Bagus Wahyu (IJBLE Scientific Publications Community Inc., 2021)
The existence of internet in modern era makes society easy to do their activities. All aspect of human life is based on online or connected to internet. The development of e-administration in school administration is one of them. This study was descriptive qualitative which aims to describe and to explain school administration concept based online to ease school management in digital era. Source of data divided into two, including document and informants referring to education expert, education implementer unit and society as education user. Technique of collecting the data were content analysis and in-depth interview. Triangulation of source of data technique were used to validate the data. The result shows that there are some school administration system based online to ease school administration process. They are school registration based online (e-registration), school payment based online integrated with certain bank account (e-school payment), teaching journal based online (e-journal), and student achievement report based online (e-raport). Besides, school is also facilitated by school administrator which can be contacted via whatsapp and telegram applications to ease education user on asking for information about school and education